Effect of weathering on disintegration and shear strength reduction of clay shale - Alatas, I. M. (Penerbit UTM Press, 2016)
Frequent and strong atmosphere and hydrosphere reactions accelerate weathering of clay shale. This study was carried out to determine the effects of frequent natural drying and wetting-drying cycles on clay shales in every 8 days until the value of disintegration ratio, DR reached zero (completely non-durable). Clay shale samples from Semarang-Bawen and Hambalang were tested in the laboratory under four circumstances: (1) without soaking, (2) soaked once in every 8 days, (3) soaked 2 times in every 8 day and (4) soaked 3 times in every 8 days. Disintegration ratio, DR was obtained from the change in grain size distribution of the clay shale due to weathering. Reductions in shear strength of the samples were observed after subjected to wetting-drying cycles. The DR of Semarang-Bawen clay shale reached zero after 32 days, while the DR of Hambalang clay shale showed a range of values between 0.09 and 0.147 on the 80th day. Wetting-drying cycles showed greater impact than natural drying on shear strength parameters reduction. Triaxial tests could only be performed on samples from Semarang-Bawen and Hambalang which were exposed to wetting-drying cycles up to 24 and 32 days of test, respectively beyond which the samples completely disintegrated.